Preparation and thermal properties of Alkoxy Silane functionalized polyether sulfone/well-defined poly(trimethoxysilyl) propyl methacrylate-based hybrid materials - OKTAY, BURCU; KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (WILEY, 2018)
In this study, novel polyethersulfone (PES) and poly(trimethoxysilyl) propyl methacrylate (PMPS) containing hybrid materials were prepared. PES was functionalized with trimethoxysilane groups by UV-induced grafting reaction. PMPS was synthesized by atom transfer radical polymerization. In the followed process, the functionalized PES mixed with different amount of PMPS, thermally treated to promote sol-gel crosslinking process to prepare the PES-based hybrid materials. The trimethoxysilane grafted PES chains are covalently bonded with the well-defined trimethoxysilane groups of PMPS. The chemical structure of the prepared PES and PMPS is confirmed by Fourier transform infrared analysis. The morphology of the hybrids was investigated by scanning electron microscopy. The results of thermogravimetric analysis show that the thermal stability of the hybrid materials was significantly affected with the addition of PMPS. POLYM. ENG. SCI., 58:1346-1352, 2018. (c) 2017 Society of Plastics Engineers
Keywords: ULTRAFILTRATION MEMBRANES; POLYMERIZATION; MORPHOLOGY; PARTICLES; UV